Efisiensi dan Efektivitas Pengelolaan Penerimaan Pajak untuk Pembangunan Ekonomi di Indonesia - Lusia Lestina Halawa; Mira Sukma; Evlin Limbong; Wahjoe Pangestoeti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the level of efficiency and effectiveness in managing tax revenues in Indonesia and its contribution to national economic development. Taxes are the primary source of state funding and play a crucial role in supporting development programs and welfare distribution. However, there remains a gap between tax potential and realization, indicating the need to evaluate the current tax administration system. This research adopts a descriptive quantitative approach using secondary data from DJP, BPS, and the Ministry of Finance covering the 2019–2023 period. The findings show that tax collection effectiveness has been relatively high in the last two years, as indicated by revenue realization exceeding targets. Nevertheless, efficiency remains low due to suboptimal digital systems and limitations in human resource capacity. Effectiveness is also strongly influenced by information technology and the performance of tax officials. The study concludes that tax reform focused on digitalization and transparency must be strengthened to support sustainable economic development. These findings have important implications for future fiscal policies and suggest opportunities for further research using mixed-method approaches.